Development of a Portable Disaster Evacuation Simulation Tool for Elementary Schools Using Quality Function Deployment (QFD) - Febrianto, Ahmad Janan; Aji, Dody Bimo; Zulfiar, Muhammad Heri (Universitas Sarjanawiyata Tamansiswa, 2024)
This study presents the development of an interactive, portable disaster evacuation simulation tool for elementary school students using the Quality Function Deployment (QFD) method. The tool aims to enhance student's ability to memorize and recall evacuation routes through hands-on learning and interactive play. Conducted as a case study in a private elementary school in Bantul, Yogyakarta, this research integrates the House of Quality (HoQ) framework to align technical specifications with educators' requirements. The simulation tool is designed as a modular labyrinth-style board that mimics the school's disaster evacuation map, allowing students to actively reconstruct escape routes and improve their spatial awareness and disaster preparedness. Findings reveal that the interactive and adaptable nature of the tool significantly improves students' understanding of evacuation procedures compared to traditional static evacuation maps. Additionally, the tool's portability and customizable design accommodate annual changes in school infrastructure, ensuring long-term usability and scalability. This study highlights the importance of incorporating game-based learning and interactive disaster education strategies into school curricula, promoting engaged learning and better emergency preparedness among young learners.